From research methodology to the analysis of the socio-spatial fragmentation process in Brazilian cities - Sposito, Maria Encarnacao Beltrao [UNESP]; Catalao, Igor (Estudios Sociologicos Editora, 2024)
Conducting research in social sciences poses many challenges to researchers, especially regarding the definitions of methodological nature. This is particularly challenging when it comes to working with material produced from qualitative procedures. In addition to outlining the aspects that relate to how carry out the research - for example, who will be interviewed and where, what script will be used, what contexts to conduct an interview, what precautions to take etc. -, one must also specify the methods of analysis of the contents produced. Based on a research carried out in ten Brazilian urban areas on the theme of socio-spatial fragmentation, this article proposes a way to analyse the contents of interviews with city dwellers. To this end, the general framework of the research is presented - including objectives, method, and methodological procedures - to then develop a proposal for analysis based on three categories originally developed by the French researcher Herv & eacute; Breton to interpret narratives: spatiotemporal, experiential, and inferential. Although the proposed methodology for interpreting recorded narratives is based on interviews carried out in ten Brazilian urban areas, in this article, only one example is presented, related to the analysis of one of the cities carried out in Chapec & oacute;, a city in the state of Santa Catarina. The text is concluded with some summary notes.
Keywords: socio-spatial fragmentation; qualitative methodology; interpretation categories; Brazilian cities